THE SNAPPER (LUTJANIDAE) OF SPERMONDE ARCHIPELAGO, SOUTH SULAWESI - Andi Iqbal Burhanuddin; Yukio Iwatsuki (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
Fish diversity monitoring could be used as a basis for formulating management of the fisheries resources. This study was conducted to describe the snapper of the family Lutjanidae from the Spermonde Archipelago, South Sulawesi. Specimens were collected in Rajawali and Paotere Fish Landing Port Makassar, South Sulawesi from November 2005 to August 2009. The result showed that there was 42 species representing eight genera of family Lutjanidae inhabiting the area were examined and identified: Aphareus furca, A. rutilans, Aprion virescens, Etelis carbunculus, E. radiosus, Lut-janus argentimaculatus, L. bengalensis, L. biguttatus, L. bohar, L. boutton, L. carponotatus, L. decussatus, L. fulvus, L. sebae, L. fulviflamma, L. fuscescens. L. johnii, L. kasmira, L. gibbus, L. lemniscatus, L. lunulatus, L. lutjanus, L. mala-baricus, L. monostigma, L. quinquelineatus, L. rivulatus, L. russelli, L. sebae, L. timorensis, L. vitta, Macolor macularis, M. niger, Paracaesio kusakarii, Pristipomoides argyrogrammicus, P. auricilla, P. filamentosus, P. flavipinnis, P. mul-tidens, P. typus, P. zonatus, Symphorichthys spilurus, S. nematophorus. The local name available of each species was given.